Audiovisual Aids to Develop Listening and Speaking Skills in Eighth Grade at Genesis School 2023 - Artola Pérez, Albin José; Cubas, Ronald Javier (Nicaragua, 2023)
Ayudas, audiovisuales, desarrollar habilidades auditivas, orales
Incluye: bibliografía, índice
Col. Educ.
Keywords: 1. EDUCACIÓN 2. ENSEÑANZAS 3. HERRAMIENTAS TECNOLÓGICAS